The Science Learning Material Using PjBL Model Integrated with Science, Technology, Engineering, and Mathematics (STEM) Approaches to Enhance Students' Communication Skills - Sri Yamtinah; Hariyanto Hariyanto; Sukarmin Sukarmin; Sulistyo Saputro (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
This study aims to develop a science learning material using PjBL model integrated STEM approaches to enhance students' communication skills. The method used is the 4D Research and Development (R&D) model and an experimental method for testing the effectiveness of the device. The study population was all VII class in one of the junior high schools in the South Tangerang region with samples taken using a random sampling technique of 76 people. The instrument used was a device feasibility test sheet and an observation skill communication sheet. The data obtained were then analyzed quantitatively and qualitatively. The results showed the components of the learning device in the form of syllabus, lesson plans, teaching materials and student worksheets, were very feasible to use with an average of 3.62. In addition, each item validity assessment instrument is also declared valid for use. The observed communication skills also increased from 1.59 to 3.15 with a gain value of 0.64 (medium category) for the experimental class. Meanwhile, the gain value for the control class is 0.005 (very low category). The difference in the gain value indicates that the learning device is effective in improving students' communication skills.